2001
DOI: 10.1590/s0102-311x2001000200011
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para poliparasitismo intestinal em uma comunidade indígena de Pernambuco, Brasil

Abstract: An investigation into the ethno-epidemiological profile of the Pankararu indigenous group in the State of Pernambuco, Brazil, identified multiple intestinal parasites in nearly all members of the community. To detect possible environmental risk factors, we used the data base from a previous survey to test relations between daily living conditions (housing, sanitation, water supply and treatment, and garbage disposal) and the number of different parasite species found in the same household. The sample consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
21

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 12 publications
(10 reference statements)
2
16
0
21
Order By: Relevance
“…The transmission model found in Natuba is similar to those identified in studies that approach eco-epidemiology, in which the understanding of the disease cannot be dissociated from the analysis of the space in which the individual is inserted 25 . The polyparasitism shown in the present study can be understood in a similar way to previous studies [26][27][28] , in which there are the characteristics of living conditions and routine of individuals that live at sites with precarious sanitary conditions. The theme map presented by Figure 2 shows that most individuals infested by the S. mansoni live in the north region of the location.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The transmission model found in Natuba is similar to those identified in studies that approach eco-epidemiology, in which the understanding of the disease cannot be dissociated from the analysis of the space in which the individual is inserted 25 . The polyparasitism shown in the present study can be understood in a similar way to previous studies [26][27][28] , in which there are the characteristics of living conditions and routine of individuals that live at sites with precarious sanitary conditions. The theme map presented by Figure 2 shows that most individuals infested by the S. mansoni live in the north region of the location.…”
Section: Discussionsupporting
confidence: 84%
“…The search and identification of potential foci of parasite infections are extremely important to public health, given they can provide prophylactic and educational information to fight the forms of transmission and development of these conditions, mainly in regions where schistosomiasis is historically endemic, such as the Zona da Mata of Pernambuco, where several control strategies been thought of, although no advance has been sustainable enough for its control [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…10 An ethno-epidemiological description of an indigenous population of the state of São Paulo showed that polyparasitism is the rule among the subjects analyzed, being related mainly to the sources and treatment of drinking water. 5 However, a socioeconomic threshold is assumed to exist, below which sanitation measures are not sufficiently prophylactic. Such infections may also occur in the domestic environment, where sanitary education, notions of hygiene, and cultural aspects are relevant to the elimination of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of this problem has been prevented by the high costs involved in improving basic sanitation, as well as by the lack of educational programs capable of achieving community mobilization, which is fundamental for changing habits and beliefs that contribute to the mechanisms of disease transmission, and often play a role in social underdevelopment. 5,6,10,14,16 The present work was aimed at verifying domestic sewage contamination in a river and two of its affluent streams, evaluating basic sanitation conditions, and…”
Section: Introductionmentioning
confidence: 99%
“…No Rio Grande do Sul, na TI Guarita e outras áreas indígenas do estado 13,14 , essas doenças têm sido as principais causas de hospitalizações e morte em menores de cinco anos. Em populações indígenas, precárias condições de saneamento e água contaminada propiciam o poliparasitismo 35 e infecções recorrentes que, associadas a situações de carência alimentar, podem levar à desnutrição. Os resultados deste estudo sugerem que essa população vive em condições de saneamento precárias e o preparo de alimentos com água de poço, fonte ou rio, quando comparados aos que utilizam água de torneira, colocam a criança em risco de desnutrição afetando seu crescimento linear.…”
Section: As Condições De Vida Associadas à Menor Altura Dos Filhosunclassified